PORT TOPOGRAPHY IN ATLANTIC AND MEDITERRANEAN HISPANIA - Alberto Bermejo MELÉNDEZ; Javier Bermejo MELÉNDEZ; Francisco Marfil VÁZQUEZ; Juan Manuel Campos CARRASCO (Journal of Ancient History and Archaeology, 2023)
Nowadays, the study of ports in Hispania has a firmly established line of research highlighting the port configuration of numerous Atlantic and Mediterranean cities. Within this context, along the coasts of the Iberian Peninsula —as well as in the course of the main rivers— the port settlements that mark the water from the Mediterranean to the Cantabrian Sea have a series of structures or environments whose architectural elements seem to follow standard patterns in their structural systems and location that are perpetuated throughout their evolution. The common need to solve the various problems caused by maritime traffic and port activity linked to the commercial networks of an increasingly complex provincialized imperial economy seems to lie in their endowment.